Utility of Biomarkers in Sepsis: Mirror Reflection of Inner Truculent Devil (Bangladesh Journal of Medical Science, 2013)
There is a plethora of biomarkers proposed and being researched in the field of sepsis. The complex pathophysiology of sepsis involves many mediators of inflammation pertaining to coagulation, complement, contact system activation, inflammation, apoptosis, etc. Markers related to those processes can gauge the degree of sepsis. Compared with localized pathology, the systemic nature and involvement of multiple organs in sepsis gives scope for numerous potential biomarkers. There is no 'gold standard' for the diagnosis of sepsis. Currently available/in-research biomarkers are compared for their efficacy with methods used to diagnose and monitor sepsis such as combination of clinical signs and available laboratory variables. An arbitrary classification of these biomarkers is made and the literature surrounding these markers and their efficacy in diagnosis of sepsis is reviewed. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13349 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.17-29